Exploring health risk of people living near the Secondary Transfer Stations and Landfills in Dhaka. (30th September 2020) - Sara, H; Alam, R; Hasan, T; Quayyum, Z; Jerin, D
Abstract: Background: Proper management of increasing solid waste is a major challenge for Dhaka city. Hence, the consequences on health are numerous and depend on the nature of the waste, individuals exposed, duration of exposure and availability of interventions for those exposed. This study seeks to identify the potential health risk associated with contamination from STSs and landfills in Dhaka city. Methods: This study has adopted a multi-method approach that includes qualitative data collection and analysis of secondary spatial data. Thematic analysis was performed for analysing the qualitative data and. Spatial data were collected from the Survey of Bangladesh and analysed to show the spatial distribution of 68 STSs out of 81 STSs in Dhaka City. Results: Qualitative study suggests that the leachate migration from the landfill and STSs make the surrounding environment worse and causes health sufferings to the people living near the STS or landfill along with the people directly working. Furthermore, findings from the spatial data reveal that, 12 STSs within 50-100 meters and 54 STSs within 100 meters radius of an education institute and round 75 STSs are also located within 100 meters radius of the health facilities. Numerous settlements and natural features are also located within 500 meters of buffer zone from the both landfills. Flies and mosquitoes are breeding at a greater pace in and around the landfills where high quantities of solid waste are being dumped. Again, waterlogging is very common due to the dumping of waste which in turn is causing the spread of dengue and other water borne diseases in the surrounding area. Conclusions: Poor management and incautious allocation of the STSs and landfills have adverse effects on the people's health residing nearby. Managing waste in the landfill and STS with a proper manner, and engaging more manpower with adequate safety equipment could be a great help to reduce the health sufferings of the people living nearby. Key messages: Improper solid waste management practice effects on the health of people residing near the STSs and landfills. To manage the waste of the STSs and landfills in an efficient way and not cause daily nuisance to the nearby residents.